Open-end investment funds in the E.E.C. and Switzerland - Corner, D. C.; Stafford, D. C. (London : MacMillan Press, 1977)
This book deals with the types of investment fund that make continuous issues of new shares in response to public demand, and that are prepared to redeem their shares at net asset value. They are generally known as open-end investment funds or, in North America as mutual funds.
Includes index.
Bibliography: p. [244]-250.
usc 20/9/17
Loans
Keywords: Mutual funds; Europe--European Economic Community countries; Switzerland